Sailing into a dilemma: An economic and legal analysis of an EU trading scheme for maritime emissions - Claudia Hermeling; Jan Henrik Klement; Simon Koesler; Jonathan Köhler; Dorothee Klement (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
On the basis of a joint economic and legal analysis, we evaluate the effects of a 'regional' (European) emission trading scheme aiming at reducing emissions of international shipping. The focus lies on the question which share of emissions from maritime transport activities to and from the EU can and should be included in such a system. Our findings suggest that the attempt to implement an EU maritime ETS runs into a dilemma. It is not possible to design a system that achieves emission reductions in a cost efficient manner and is compatible with international law.
Keywords: L91; Q58; R48; 330; emission trading; international shipping; maritime emissions; regional emission trading; international jurisdiction for emission trading schemes